Psychiatric Disorders of Neurocysticercosis: Narrative Review - El-Kady AM (Dove Medical Press, 2021)
Asmaa M El-Kady,1 Khaled S Allemailem,2 Ahmad Almatroudi,2 Birgit Abler,3 Mohamed Elsayed3 1Department of Medical Parasitology, Faculty of Medicine, South Valley University, Qena, Egypt; 2Department of Medical Laboratories, College of Applied Medical Sciences, Qassim University, Buraydah, Saudi Arabia; 3Department of Psychiatry and Psychotherapy III, University of Ulm, Ulm, 89075, GermanyCorrespondence: Asmaa M El-KadyDepartment of Medical Parasitology, Faculty of Medicine, South Valley University, Qena, EgyptTel +201114229741Email Asmaa.elkady@med.svu.edu.egAbstract: Neurocysticercosis, the most common type of neuroparasitosis, is a condition in which the central nervous system (CNS) is infested with the pork tapeworm Taenia solium cysticercosis’ larvae. Neurocysticercosis is the most widespread parasitic CNS disease worldwide, affecting more than 50 million individuals. As neurocysticercosis is prevalent in developing countries, the growing number of migrants and travelers increases prevalence in developed countries. Possible neuropsychiatric manifestations are depression, cognitive dysfunction, dementia, and visual hallucinations. Depending on the cysts’ location in the CNS, focal neurology or psychiatric symptoms manifest. The diagnosis of neurocysticercosis is based on neuroimaging and serology. The correlation between specific symptoms and the cyst’s location might help better understand psychiatric disorders’ pathophysiology. Nonetheless, the exact prevalence of neurocysticercosis is seldom reported in patients with psychiatric disorders, which may be due to the lack of imaging availability in developing countries with a high prevalence.Keywords: psychiatric, neurocysticercosis, cognitive functions, depression, dementia